Effectiveness of group film therapy on happiness and quality of life among elderly adults of Kahrizak nursing home - Farnosh-asadat Hosseini; Anahita Khodabakhshi-Kolaee; Davood Taghvaee (Mashhad University of Medical Sciences, 2016)
Background and objective: The recent research has shown the efficacy of happiness and quality of life on mental and physical health. In addition, considering the aging population continuously increases therefore, the aim of current research is to investigate the efficacy of group film therapy on happiness and quality of life in elderly adults' women. Methods: This research is a quasi-experimental study with pre and post- tests. The population of study was Kahrizak nursing home residents. 24 elderly adults' women selected through the criteria. They were assigned randomly to the control and experimental groups. The experimental groups received film therapy for eight treatment sessions (90 minutes for one session per week). The research instruments were Oxford Happiness Index (OHI) and WHO Quality of Life-BREF (WHOQOL- BREF). Statistical analysis conducted by analysis of covariance. Results: There was significantly difference (F= 8.42, sig= 0.009) between mean's scores of pre (M=28.33) and post-test (M=53) of happiness of experimental group among elderly adults. Also, it was not observed significantly difference (F=3.11, sig= 0.09) between mean's scores of pre (M=99.5) and post-tests (M=105.7) of life quality of experimental group among elderlies. Conclusion: Film therapy has positive effects on happiness and moderately on quality of life in older adults. Hence, film therapy could be considered as an alternative or complementary approach to existing therapies for enhancing happiness among elderly adults. Paper Type: Research Article.